Los programas pioneros de educación inicial no escolarizada del Perú y su impacto en la superación de desigualdad educativas de las mujeres - Llanos Zuloaga, Martha (2016)
This document constitutes an update of the original document written for the Regional Meeting organized by UNESCO-OREALC to focus on and consider alternatives related to Women’s Education in Latin America. I was invited to Panama to share with colleagues the perspectives on this matter. Due to having had a direct and pioneering participation in the non-formal education of the programs in Peru and in Latin America, I was selected to share these experiences. At present, I think it is appropriate to carry out 30 years later, an update with a comprehensive verification of PRONOEI impact not only including boys and girls who are the fundamental objective of these programs but mainly all participating actors which are about 99% women. Preliminaries contributions are abridged in Braslavsky (1984).